Developing a norm for screening athletes during competitions: Nigerian Secondary Schools Sports Federation experience (2001)
In an attempt to find solution to cheating which characterizes age-declaration at many age-group competitions, various methods including chronological age and physiological age (skeletal age) have been adopted to ascertain what is called “truly” “under-18” for secondary school sports competition. But rather than solving the problem, these methods seem to have created more problems. This study then ventured into another method which pull together the use of the above two stated method into one. The method called exponent system was tested and eventually adopted successfully during the 1998, All Nigeria Secondary School Sports Federation Competition held in Abuja.